Konsepsi Sekolah Islam Terpadu: Integrasi Pendidikan dan Nilai-nilai Agama - Abdul Latif Rahman; Arif Sabekti; Faradila Amalia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The Integrated Islamic School concept represents an educational approach that integrates a secular curriculum with Islamic values ​​in an educational environment. This approach aims to create a holistic learning environment, where students' academic, spiritual and moral aspects are the main focus. This research explores the implementation and impact of the Integrated Islamic School concept, highlighting how the integration of religious values ​​in the curriculum can influence students' overall development. The research method used for analysis is descriptive from literature and case studies from several Integrated Islamic Schools that have implemented this concept. It is hoped that the results of this research will provide a deeper understanding of the importance of integrating religious values ​​in the context of modern education.